SUMBER DAYA GURU DALAM IMPLEMENTASI KEBIJAKAN KARAKTER DI SEKOLAH SMPN 1 PLOSOKLATEN KEDIRI - Iis Maulah (Universitas Muhammadiyah Purwokerto, 2018)
One of the great challenges that must be faced and soon resolved in Indonesia is the character of the learner. Therefore, school education has an important role in building the character of students in Indonesia. This study aims to determine the teacher resources in the implementation of character education policy in SMPN 1 Plosoklaten. This research is a qualitative research with case study approach. The results of this study indicate that the existing teacher resources in Plosoklaten still require guidance and supervision, because the implementation of the policy listed in Permendikbud No. 23 2016 still as a formality, so the character of students in SMPN 1 Plosoklaten still not maximal. Keywords: teacher resources, policy implementation, character education